Semantic adaptations of the Arabic loanwords in the Indonesian language - Ali Ahmed Julul; Nabilah Myrrha Rahmawati; Deny Arnos Kwary; Ni Wayan Sartini (MOZAIK HUMANIORA, 2019)
This paper investigates the adaptation of Arabic loanwords in the Indonesian language semantically. The data were taken from Kamus Basar Bahasa Indonesia (KBBI) fifth edition. 1,870 words are listed in the KBBI as Arabic loan words. The definitions of these words were compared with their original Arabic definitions found in Almaany Arabic dictionary (2019) to determine the semantic adaptations. The analysis shows that most of the Arabic loanwords in the Indonesian language have retained the same meanings as their originals in the Arabic language. However, there have been semantic adaptations in which eighteen words have been narrowed, nine words have been extended, and seven words have gone through the shifting process. The narrowing was due to absorbing of only one meaning of a word that had many meanings in Arabic ,  borrowing the old meanings of the words that have been extended recently due to the advent of technology, filling any existing gap or borrowing of new words along with cultural concepts. The extending was due to overgeneralizing some Arabic affixes and forms ,leaving one form of a word to represent the meanings of the others or assigning names to things by the way people perceive them by their five senses . The shifting occurred mainly because of borrowing of new words along with cultural concepts, assigning names to things by the way they are perceived by the five senses or overgeneralizing of forms that occurred in Arabic loanwords.It is hoped that the findings of this study will be useful to researchers interested in semantic adaptation of loanwords.